Associação de fadiga cíclica, biocorrosão e fricção na formação microestrutural de lesões cervicais não cariosas - Zeola, Livia Fávaro (2015)
Non carious cervical lesions (NCCLs) are routine findings in clinical practice and are described as the loss of tooth tissue close to the cementum enamel junction. NCCLs have multifactorial etiology with main factors involved are stress, biocorrosion and friction. The different associations of these factors can lead to the weakening of the tooth structure in the cervical region, generating NCCLs. The aim of this study was to evaluate the association of etiologic factors (stress, biocorrosion and friction) on the microstructural formation of NCCLs, using finite element analysis, laser confocal microscopy and computed microtomography (micro-CT). Two three dimensional (3D), linear and elastic models of mandibular premolars were generated for stress distribution evaluation, using the finite element analysis (FEA). Two oblique loadings (50 N), were applied on the buccal cusp slope of the model. The occlusal loading (CO) was applied on the grinding region of the buccal cusp and the buccal loading (CV) on the smooth region of the same cusp. Both loads were applied at 45̊ to the tooth long axis, simulating mandibular excursive movements. The displacement restriction was applied on the base and lateral surface of the model and the results were analyzed by the maximum principal criteria. Then, for analysis by confocal microscopy, forty intact human mandibular premolars were selected and allocated randomly into four groups, according to the factor association type (n=10): (TB) stress-biocorrosion, (TF) stress-friction, (BF) biocorrosion-friction, and (TBF) stress-biocorrosion-friction. In each group, the challenges were performed in an alternate way. The stress was simulated by cyclic fatigue loading, with specimens positioned in mechanical fatigue machine and subjected to oblique load (50N), on the smooth region of the buccal cusp for 6 x 105 cycles. The biocorrosive challenge was performed using the application of hydrochloric acid (2mL/10s). The friction (abrasion) was reproduced by using electric/powered toothbrushes (300g/20s), with Colgate Total 12 toothpaste. The roughness surface, angle and height of steps were measured before and after the treatments, using a 3D laser confocal microscope. The data were analyzed using the paired t-test, two-way analysis of variance and Tukey s test (α=0.05). Then, three specimens of each group were taken to a micro-CT for the qualitative analyses. The CV loading promoted higher concentration of tensile stress in the cervical region compared to CO. The presence of biocorrosion was an important factor to roughness changes and abrasion promoted similar behavior among the groups. The TBF association promoted the greatest alterations in tooth structures. Enamel and dentin showed distinct performance according to the different interactions. The FEA results presented relationship with the experimental findings for TF,TB, TBF groups. The TBF was the more influent association on the microstructural formation of NCCLs, for enamel. For dentin, the association of at least two factors was sufficient to generate significant tissue degradation. All studied associations of etiological factors showed potential to promote NCCLs formation.